Development of a method for the determination of amanitin and phaloidin toxins in Amanita fungi and in human urine - Leschev, Sergey M.; Pakhadnia, Yury G.; Ahabalayeu, Aliaksandr A.; Shahoika, Pavel G.; Zayats, Mikhail F. (Journal of the Belarusian State University. Chemistry, 2023)
At the temperature (20 ± 1) °C, the extraction of amanitin (α-amanitin, β-amanitin) and phalloidin (phalloidin and phallocidin) toxins with butanol from water and with butanol and isopropanol from aqueous solutions of ammonium sulfate and potassium hydrogen phosphate was studied. On the basis of the obtained experimental data, the distribution constants of toxins were calculated, which were used to develop a technique for extraction sample preparation in the process of determining toxins in fungal material and human urine. It has been shown that for the extraction of amanitin and phalloidin toxins from various objects with a high water content, it is advisable to use extraction with butanol using salting out with ammonium sulfate up to saturated solutions. Extraction techniques have been developed for sample preparation of fungal material and human urine for the subsequent determination of toxins in them by liquid chromatography with mass spectrometric detectors such as «triple quadrupole» and «quadrupole – orbital trap». The technique for the determination of toxins in urine is characterised by a limit of quantification of about 1 ng/mL of urine, the technique for the determination of toxins in mushroom material – 600 ng in 1 g of dry mushrooms. The relative standard deviation of the determination of toxins is about 25 %.